Copy letter from Roger Casement to Gertrude Bannister, having returned from a holiday in Buenos Aires which he much prefers over Brazil: "Brazil and the Brazilians are vile" - Casement, Roger, 1864-1916; Bannister, Gertrude, d. 1950 (1907)
He discusses the ongoing Congo question and doubts that the annexation of the Congo by Belgian will accomplish much.
Typescript copy with correction in black ink, addressed from: "Santos".
Keywords: Casement, Roger, -- 1864-1916 -- Correspondence; Bannister, Gertrude, -- d. 1950 -- Correspondence; Léopold -- II, -- King of the Belgians, -- 1835-1909; Imperialism; Diplomatic and consular service, British; Brazil; Congo (Democratic Republic)